2006
DOI: 10.1136/jnnp.2005.079053
|View full text |Cite
|
Sign up to set email alerts
|

Pain and motor complications in Parkinson's disease

Abstract: Aims: To study the association of pain with motor complications in 117 patients with Parkinson's disease. Methods: Patients were asked to refer any pain they experienced at the time of study and lasting since at least 2 months. Basic parkinsonian signs and motor complications (including motor fluctuations and dyskinesia) were assessed and Unified Parkinson's Disease Rating Scale (UPDRS) motor score part III (during on) and part IV were calculated. Information on age, sex, duration of disease, use of dopamine a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

11
158
6
8

Year Published

2007
2007
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 201 publications
(183 citation statements)
references
References 23 publications
11
158
6
8
Order By: Relevance
“…This difference was not made clear on the motor analysis by UPDRS, which was similar between the patients with and without pain, as observed in a recent study 16 , contrary to two previous studies 17,18 that demonstrated motor fluctuations between the groups with and without complaints of pain.…”
Section: Discussioncontrasting
confidence: 93%
“…This difference was not made clear on the motor analysis by UPDRS, which was similar between the patients with and without pain, as observed in a recent study 16 , contrary to two previous studies 17,18 that demonstrated motor fluctuations between the groups with and without complaints of pain.…”
Section: Discussioncontrasting
confidence: 93%
“…Pain has been more deeply studied in recent years as a PD symptom which substantially affects QL of at least one third of patients 11 . Considering our results, mean age of studied population and presence of pain, there has been no correlation, similarly to literature reports [12][13][14] . Fill et al 4 have carried out a detailed literature review evaluating possible mechanisms, classifications and potential risk factors for PD pain, and have observed that age was not systematically considered in all studies and that correlation between different types of pain and age was not investigated in some studies.…”
Section: Discussionsupporting
confidence: 83%
“…In advanced stages, pain may be caused by motor fluctuations (dyskinesia or off-period dystonia), and may be radicular or due to musculoskeletal problems [27,28]. In most of the published work, pain in PD was found to be related to a musculoskeletal cause or dystonia [1,3,29,30,31,32]. Musculoskeletal pain (44.4%) and dystonia-related pain (19.1%) were the most common types of pain (table 4).…”
Section: Discussionmentioning
confidence: 99%
“…Musculoskeletal pain (44.4%) and dystonia-related pain (19.1%) were the most common types of pain (table 4). Musculoskeletal problems are common in patients with PD, and in some studies, appear to be related to the presence of rigidity and akinesia [30]. One of the most common musculoskeletal problems in PD is shoulder stiffness, and a stiff shoulder may be the first sign of PD.…”
Section: Discussionmentioning
confidence: 99%